Board effectiveness, managerial ownership and company performance - Md Kassim, Aza Azlina; Ishak, Zuaini; Abdul Manaf, Nor Aziah (2012)
The study examines the effects of board process and managerial ownership on company performance of Malaysian public listed companies.Unlike traditional governance models that emphasize on board structure, this study focuses on board process.Two types of data are used; a survey to Malaysian directors and company annual reports.In total, 175 companies responded to the questionnaires, which represent 26% of response rate.The results of the study provide evidence that board’s risks oversight and performance of independent directors are associated to company performance.The results provide feedback to the policy makers in Malaysia as the results indicate that board effectiveness influences company performance.